KUALITAS RELASI IBU-ANAK DAN HARGA DIRI PEREMPUAN EMERGING ADULTHOOD - Yenny Fabiola; Hartanti Hartanti; Ktut Dianovinina (CALYPTRA, 2018)
Self-esteem as self-worth or self-image, a global evaluation of the self has an important role in the individual development especially at the emerging adulthood. This is because at thi s stage, human have more control against their social environment. Mother-daughter relationship has the highest emotional bond. The purpose of this study is to find the correlation between mother-daughter relationship with daughter’s self-esteem in emerging adulthood. The research results show a significant positive correlation between mother-daughter relationship with daughter’s self-esteem in em erging adulthood with r = 0. 338 and p < 0,05. Th e correlation among mother-daughter relationship with four aspects of self -esteem indicate a positive correlation on aspects significance (r = 0,596 and p < 0,05) and virtue (r = 0,195 and p < 0,05 ). The conclusion f rom this research is that th ere is a positive correlation between mother-daughter relationship and daughter’s self-esteem inemerging adulthood, but it only has a minimal contribution. The advice for the next research is to cor relate father-son relationship and use male student as the subject research.